Testing many treatments within a single protocol over 10 years at MRC Clinical Trials Unit at UCL: Multi-arm, multi-stage platform, umbrella and basket protocols. (October 2017) - Parmar, Mahesh KB; Sydes, Matthew R; Cafferty, Fay H; Choodari-Oskooei, Babak; Langley, Ruth E; Brown, Louise; Phillips, Patrick PJ; Spears, Melissa R; Rowley, Sam; Kaplan, Richard; James, Nicholas D; Maughan, Timothy; et al.
There is real need to change how we do some of our clinical trials, as currently the testing and development process is too slow, too costly and too failure-prone often we find that a new treatment is no better than the current standard. Much of the focus on the development and testing pathway has been in improving the design of phase I and II trials. In this article, we present examples of new methods for improving the design of phase III trials (and the necessary lead up to them) as they are the most time-consuming and expensive part of the pathway. Key to all these methods is the aim to test many treatments and/or pose many therapeutic questions within one protocol.